2021
DOI: 10.1016/j.amsu.2021.102308
|View full text |Cite
|
Sign up to set email alerts
|

Case report of unusual cause of trigeminal neuralgia: Trigeminal neuralgia secondary to enlarged suprameatal tubercle

Abstract: Background Classic trigeminal neuralgia (TN) is caused by vessels compressing the trigeminal nerve root entry zone. The cause is usually impingement of the superior cerebellar artery, anterior inferior cerebellar artery, or a vein. Other rare causes have been reported including aneurysmal compression, skull base tumors, and vascular malformations. An enlarged suprameatal tubercle (EST) as a cause of TN has not yet been described. Case presentation We report the first ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…causing the direct bony compression of the trigeminal nerve. 15 Several factors are known to be associated with the technical difficulty of trigeminal nerve MVD, including the involvement of dolichoectatic vertebrobasilar arteries as an offending vessel, 17 well-developed SPV complexes as a vascular obstacle, 14 and enlarged SMTs as a bony obstacle. [3][4][5][6][7][8][9][10] Multivariate analysis with logistic regression, performed in the present study, indicated that an enlarged SMT and a multiple number of offending vessels are indicative of the need for SMT removal during trigeminal MVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…causing the direct bony compression of the trigeminal nerve. 15 Several factors are known to be associated with the technical difficulty of trigeminal nerve MVD, including the involvement of dolichoectatic vertebrobasilar arteries as an offending vessel, 17 well-developed SPV complexes as a vascular obstacle, 14 and enlarged SMTs as a bony obstacle. [3][4][5][6][7][8][9][10] Multivariate analysis with logistic regression, performed in the present study, indicated that an enlarged SMT and a multiple number of offending vessels are indicative of the need for SMT removal during trigeminal MVD.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical outcomes were assessed at a median follow-up duration of 3.6 years after surgery (range, 18 months-10 years), and categorized according to the Barrow Neurological Institute (BNI) pain intensity score, as follows: I-no pain; IIoccasional pain without medications; III-some pain, adequately controlled with medications; IV-some pain, not adequately controlled with medications; and V-severe pain or no pain relief with medications. 15 The study population was divided into two groups: patients who underwent SMT removal (n ¼ 20) and those who did not (n ¼ 177). Variables, including SMT height, clinical characteristics, surgical findings, and outcomes, were evaluated and compared between the two groups.…”
Section: Assessment Of Clinical Characteristics and Surgical Datamentioning
confidence: 99%